Exploring Entrepreneurial Orientation’s Impact on Innovation and Academic Performance in Malang City’s Consumer Cooperatives - Rofiaty, Rofiaty; Rahmat, Ainur Rifqi Almahdani; Nisa, Khoirun; Nurcholifah, Siti (Universitas Pendidikan Nasional, 2023)
The objects studied and the areas studied in this research are how a business can maintain sustainability and increase its business competitiveness, in this case, cooperatives in the city of Malang, as well as to grow the community's economy through the implementation of entrepreneurship-oriented strategies, the business environment towards innovation and performance strategies cooperative. The role of cooperatives in creating jobs and improving the welfare of their members with the principle that cooperatives are run